ABOUT THE UP-DATING OF THE REACTOR OF РОБС-1У TYPE PARAMETERS IN THE PROCESS OF THE ELABORATION OF THE REGULATING TABLE OF THE AUDIO FREQUENCY TRACK CIRCUITS - Razgonov, Serghiy; Shapovalov, Oleksiy (Scientific Works of Vinnytsia National Technical University, 2023)
Aim of the given study is the up-dating of the parameters of the reactor of РОБС-1У Type (Single Phase Armoured Dry Type Reactor) during the elaboration of the regulating table of the audio frequency track circuits (ATC). Audio frequency track circuits are supplied from the track circuit transformer of ПОБС -2A (TSPAD) type. Reactor SPADR-1У is used as a restrainer. The analysis of the reasons, influencing the electromagnetic parameters of the reactor of a new model, manufactured in Ukraine is carried out, testing measurements are performed, reactor parameters are recalculated, calculations of the audio frequency track circuits are made, using the updated reactor parameters. Technique. Measurements of the parameters are performed by means of teslameter. The survey of the market of the cold-rolled transformer steel GO is realized. Results. Calculations of the values of the input resistances on the terminals of the track line are carried out, complex value of the reactive resistance of the oscillating contour of SPADR-1У and capacitor Сх of the supply circuit of the audio frequency track circuits which were used for the correction of the calculations of the regulating table of ATC of the railway automation systems is recalculated. It is specified that the incorrect operation of the units of the railway automation of signaling, centralization and blocking (SCB) systems may occur as a result of the impact of the traction current on the track circuits, which use SPAGR-1У of the domestic production. Scientific novelty. Scientific novelty lies in the improvement and correction the coefficients of the formulas for ATC parameters calculation, that enabled to determine more accurately the values in the regulating table of the running line and improve the ATC operation on the used section. Relative errors of the calculations as compared with the seasonal measurements of the parameters, used at the given section did not exceed 3 – 4 % for the currents and voltage. Practical value. Recommendations, regarding the introduction of the updated coefficients in ATC calculations, where the circuit solutions with the reactors of SPADR-1У type are used, have been developed.